Theorizing Factors Mediating With the Implementation of a Patient Feedback on Safety Intervention Implemented in the Primary Care Setting. (October 2021) - Beks, Hannah; Hernan, Andrea L.; Giles, Sally; Malakellis, Mary; Mc Namara, Kevin P.; Versace, Vincent L.
Developing safety interventions using patient feedback is valuable for creating safer systems of health care. A qualitative process evaluation of a patient feedback on safety intervention was undertaken in six primary care practices. The purpose was to theorize factors mediating with the implementation of the intervention using existing theories. The intervention required practices to obtain patient feedback on safety using a validated tool and respond using quality improvement methods. Multiple methods of qualitative data collection were used, including interviews and overt observation. Abductive reasoning informed the iterative process of analysis that examined theories relevant to the intervention and setting. A theoretical framework was developed, which encompassed mediating factors grouped under three concepts: practice readiness, utilization of problem-solving skills, and agency. Theorizing mediating factors was necessary to understand the complexities of primary care practices, and to identify the essential components for implementation of the intervention on a larger scale.